ChemInform Abstract: Highly Efficient Mechanochemical N‐Arylation of Amino Alcohols and Diamines with Cu0 Powder. Issue 18 (April 2016) - Martina, Katia; Rinaldi, Laura; Baricco, Francesca; Boffa, Luisa; Cravotto, Giancarlo
Abstract: The N‐arylation of amino alcohols and diamines with iodobenzene derivatives in a planetary ball mill is investigated.